Effect of Topical 5-Fluorouracil on Lacrimal Drainage System: Histopathological Evidence from Animal Experiments and Potential Clinical Implications - Singh, Swati; Trakos, Nikolaos; Ali, Mohammad Javed (Ophthalmic Plastic and Reconstructive Surgery, 2023)
Purpose: The purpose of this study is to investigate the histopathological changes in the lacrimal drainage system of rabbits following the application of 1% topical 5-fluorouracil (5-FU) for 4 weeks. Methods: Ten eyes of 10 healthy New Zealand white rabbits were subjected to topical instillation of 1% (10 mg/mL) 5-FU, 1 drop 4 times a day for 4 weeks. Rabbits underwent a detailed ocular examination including eyelids, ocular surface, punctal, peri-punctal changes, and nasolacrimal duct patency at baseline and after 4 weeks of 5-FU. The rabbits were then sacrificed, and the eyelid, conjunctiva, lacrimal gland, and the entire lacrimal drainage system were retrieved for histopathological analysis as per standard protocols. Results: Clinically demonstrable peripunctal changes and canalicular stenosis were noted in 6 (60%, 6/10) rabbits. Two of these (20%, 2/10) had additional complete regurgitation of clear fluid, indicating a nasolacrimal duct obstruction. The remaining 4 (40%, 4/10) clinically did not demonstrate lacrimal drainage changes and were patent on irrigation. The conjunctiva showed focal loss of goblet cells in several areas. Significant changes were noted in the canalicular, lacrimal sac, and the nasolacrimal duct tissues in the form of epithelial hyperplasia, subepithelial inflammation, edema, dilated and congested vessels, and fibrosis. The lacrimal gland, eyelid tissue (excluding tarsal conjunctiva), and cornea showed no significant histopathological changes. Conclusions: Clinical and histopathological changes were noted in the lacrimal drainage system of rabbits subjected to topical 5-FU application. These findings can have potential clinical implications for patients receiving 5-FU therapy.
CRIS-Team Scopus Importer:2023-06-02